Norwegian Developments and Perspectives on Violence Risk Assessment. (December 2014) - Bjørkly, Stål; Hartvig, Pål; Roaldset, John Olav; Singh, Jay P.
The first Norwegian tools designed to assess the violence risk of the mentally ill were developed in the late 1980s, though the first national guidelines for both violence and suicide risk assessment were not published until two decades later in 2007. This article reviews the history of the field of forensic risk assessment in Norway from its humble beginnings to the present day. First an overview is provided of the history of forensic psychiatry and the criminal justice system. The main scope, however, is to discuss current research on and practice of risk assessment of violence in Norway, with an emphasis on the development and use of Norwegian risk assessment tools and methods. Particular attention is paid to instruments that follow the structured professional judgment model of risk assessment, as actuarial tools are rarely researched and not routinely implemented in clinical practice in Norway. Finally, a brief analysis is provided of some controversies concerning risk assessment in the expert witness reports on Anders Behring Breivik, who murdered 77 persons in 2011.